Psikedukasi : Sosiaisasi Dampak Kriminal Bullying Sesuai UU Yang Ada Terhadap Siswa SMP Maria Monica Bekasi Bagi Kesehatan Mental - Alsa Zahra Fahira; Ferdy Muzammil; Angellita Arnettha Putri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Bullying and intimidation are several forms of bullying that we often encounter on campus, neighbors and in the office, especially in the school environment. Bullying can be done in various ways, including physical, mental and social media. The targets of bullying are usually accepted or experienced by weak people who cannot resist these actions. Bullying itself is regulated in article 76C of Law Number 35 of 2014. The focus of the problem that we will examine is "Psychoeducation: Socialization of the impact of criminal bullying in accordance with existing laws on Santa Maria Monica Middle School Students for Mental Health" with the aim of preventing bullying behavior that often occurs in the school environment. The method we will use in this research is psychoeducation or socialization which we explained in the counseling. The impact of the activities we provide is that students at SANTA MARIA MONICA SMP get deeper knowledge about the dangers of bullying behavior on a person's mental health. Apart from that, understanding how to prevent and deal with bullying behavior.